Audit Effort and Pricing Differences among the Large Audit Firms: Evidence from a Public Sector Setting. (27th August 2013) - Bradbury, Michael E.; Botica Redmayne, Nives
<x xml:space="preserve">Abstract</x> This study examines differences in audit fees and fee components (i.e., audit hours and billing rates) among the big five auditors (BIG5) in a for‐profit, public sector setting. Most prior audit hours literature employs evidence from a single auditor. As we employ evidence from all BIG5 auditors, we are able to generalize the results of prior research. We show that higher financial risk increases the number of audit hours but not fee per hours and that a different mix of audit hours and billing rates is used to audit different industries. This suggests that it is important to control for industry in future audit effort studies. We also show that the BIG5 auditors have similar audit fees. However, within the BIG5, auditors employ a different mix of audit hours and billing rates and we show that this difference reflects whether the auditors are classified as structured or unstructured. These results should be interpreted in the light of the limitations of this study, which include the small sample size, the public sector setting and the classification of auditors as structured or unstructured.